HUBUNGAN SENAM HAMIL DENGAN LAMA PROSES PERSALINAN DI DESA TAMBAHARJO: The Relationship Between Pregnancy Exercise And The Length Of The Labor Process In Tambaharjo Village - Tsuwaibatul Aslamiyyah (Jurnal Ilmiah Kebidanan (Scientific Journal of Midwifery), 2022)
Pregnancy exercise is a form of structured exercise or exercise. The labor process has factors that can affect the delivery, doing a pregnancy exercise routine is proven to be able to affect the length of the labor process, because the movement of the pregnancy exercise itself focuses on training the muscles and breathing in preparing for childbirth. The purpose of this study was to determine the relationship between pregnancy exercise and the length of the labor process in Tambaharjo Village, Pati District, Pati Regency. This type of research is an analytic survey with a retrospective method. The populations of this study were 30 postpartum mothers in Tambaharjo Village, Pati District, Pati Regency. The sampling technique is Total Sampling with 30 samples. The instruments used to collect data are questionnaires and Chi-Square data analysis. The results showed that respondents who did pregnancy exercise routine and had a standard delivery process were (67%), while those who did pregnancy exercise were not routine and had a standard delivery (7%). Statistical test shows the Chi-Square count value is 9.355>3.481 and the p-value is 0.002<0.05 so Ha is accepted. There is a relationship between Pregnancy Exercise and the Length of the Labor Process in Tambaharjo Village, Pati District, Pati Regency.